2017
DOI: 10.1101/132399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A horizontally transferred autonomous Helitron became a full polydnavirus segment inCotesia vestalis

Abstract: Bracoviruses associate symbiotically with thousands of parasitoid wasp species in the family Braconidae, working as virulence gene vectors, and allowing the development of wasp larvae within hosts. These viruses are composed by multiple DNA circles that are packaged into infective particles and injected together with wasp's eggs during parasitization. One of the viral segments of Cotesia vestalis bracovirus contains a gene that has been previously described as a helicase of unknown origin. Here we demonstrate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…For example, Helitrons have been estimated to span around 6% of the little brown bat genome and about 4% of the silkworm genome (20,21). Numerous reports revealed that Helitrons can capture genes and lead to horizontal transfer and genome shuffling, making them significant sources for genome dynamics and evolution (18,(22)(23)(24). While their evolutionary significance is undebated, HLEs are still tricky to identify efficiently because they do not create target site duplication (TSD) upon transposition and lack classical structural features (1,8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Helitrons have been estimated to span around 6% of the little brown bat genome and about 4% of the silkworm genome (20,21). Numerous reports revealed that Helitrons can capture genes and lead to horizontal transfer and genome shuffling, making them significant sources for genome dynamics and evolution (18,(22)(23)(24). While their evolutionary significance is undebated, HLEs are still tricky to identify efficiently because they do not create target site duplication (TSD) upon transposition and lack classical structural features (1,8).…”
Section: Introductionmentioning
confidence: 99%